Engineering the Future: TESEA's Commitment to Quality and Innovation (2024)
Deputy Editor Oscar Acevedo discusses the journal's most recent achievements and commitment to quality and innovation. The editorial highlights TESEA's inclusion in SCOPUS in 2023, its Q4 ranking in the Scimago Journal Rank (SJR), and its acceptance for indexing in the Directory for Open Access Journals (DOAJ).